(untitled) (Research, Society and Development, 2023)
Aim: To Map the paths taken for the production of the diagnosis from the perspective of a subjective production of care. Methodology: The research is of a qualitative nature and the semi-structured interview was used as a data production tool applied in Family Health Units a General Hospital in a capital of the Brazilian Northeast. 23 participants were interviewed, including users and health professionals, and content analysis was chosen for data production. Results: The care network is still fragmented, presenting significant access barriers that make diagnosis difficult and this has consequences in the lives of users and the recognition of the encounter and its effects on care as something powerful to be explored and can effectively contribute to the diagnostic production. Final considerations: The production of the diagnosis faces challenges due to the difficulty of access and the subjective dimension reveals itself as a strategy to be valued for health care to be comprehensive.